PENGARUH MODEL PEMBELAJARAN INKUIRI TERBIMBING TERHADAP HASIL BELAJAR FISIKA DI SMA - Wildah Maulidatul Hosnah; subiki subiki; Sudarti sudarti (JURNAL PEMBELAJARAN FISIKA, 2017)
This research related on the influence of Guided Inquiry learning model for learning outcomes physics in SMA. The purpose of this research were: 1) to examines the significance of the effect of Guided Inquiry model on the activities of students studying physics; and 2) to examines the significance of the effect of Guided Inquiry model on the cognitive learning physics students. Kind of this research is experiment by post-test only control design. Population of this research is 10th at SMAN 1 Wongsorejo. Technique to the collection of data were: test, observation, documentation, and interviews. Technique to data analysis were: Independent-sample T-test (parametric test). The results showed that there were significant differences between student’s learning activities physics experimental class and control class with value Sig.(1-tailed) < 0.05 was 0.000. Meanwhile, the results also showed that there were significant differences between the cognitive learning physics class students experiment and control class with value Sig. (1-tailed) < 0.05 was 0.000. The research can be concluded that: (1) guided inquiry learning model significantly influence the activity of students studying physics in SMA; and (2) guided inquiry learning model a significant effect on the cognitive learning physics students in SMA. Keywords: Guided Inquiry Learning Model, Student’s Physics Learning Activities, The Cognitive Learning Physics Students.